Evaluation of QIAreach QuantiFERON-TB lateral-flow nanoparticle fluorescence assay for TB infection diagnosis among TB household contacts in three high-burden settings - Thobani Ntshiqa; Akinlolu Fasanmi; Jeniffer Nagudi; Lindiwe Tsope; Andrew Copas; Stacie Stender; Issa Sabi; Elias Nyanda Ntinginya; Julieth Lalashowi; Manthomeng Matete; Lula Budiaki; Malebo Mahlalela; et al. (PLoS ONE, 2025)
Background Tuberculosis infection (TBI) testing, and treatment are fundamental to achieve TB elimination. TBI testing among close or household contacts (HHCs) has been limited, in part due to perceived complexity and high operational cost. We evaluated the performance of a new near-patient and field-based QIAreach QuantiFERON-TB (QIAreach) against QuantiFERON-TB-Gold-Plus (QFT-Plus) among HHCs of people with TB. Methods A cross-sectional study was conducted from July 2021 to September 2022 in Lesotho, South Africa and Tanzania. Blood samples were collected from HHCs for paired QFT-Plus and QIAreach processing, testing and interpretation. To evaluate the performance of QIAreach against QFT-Plus as a reference, we determined the: i) prevalence of TBI, ii) total concordance using Cohen’s Kappa, iii) predictors of discordant results using logistic regression, and iv) relationship between time to results and interferon-gamma (IFN-γ) response levels using linear correlation. Results Out of 964 enrolled HHCs, 464 had paired results, of whom 64.9% (302/465) were female with a cohort median age of 27 years (interquartile range (IQR): 13–45). Overall, 50.9% (236/464) tested positive on QFT-Plus, while 57.1% (265/464) were positive on QIAreach assay. Total concordance between QFT-Plus and QIAreach was 78.4% [353/450, 95% confidence interval (CI): 74.4–82.2, Cohen’s Kappa: 0.5627, p < 0.001]. Discordance between assays was 23.9% (111/464) and was associated with Lesotho site (adjusted odds ratio 2.70, 95%CI: 1.48–4.92, p = 0.001). HHCs with higher IFN-γ response (QFT-Plus) (≥0.35 IU.ml-l) had a shorter time to results on QIAreach. In addition, a strong negative correlation between QIAreach time to results and IFN-γ response (QFT-Plus) levels (R = −0.64, 95% CI: −0.87 to −0.41, p < 0.001) was observed. Conclusion QIAreach demonstrated a moderate concordance against QFT-Plus among HHCs in three high-burden countries. Further work is needed to understand and improve its usability in high TB and low resource settings.